A new method of measuring the oil–air–water three-phase flow rate. Issue 1 (2nd January 2020) - Wang, Yanjun; Li, Haoyu; Liu, Xingbin; Li, Lei; Huang, Chunhui; Hu, Jinhai
Abstract: Oil–air–water three-phase flow patterns in small-diameter vertical measurement channels are complex, making it difficult to establish techniques for interpretation of logging information. In this study, dynamic experiments involving oil–air–water three-phase flows were performed using a novel production logging tool that combined a petal-type turbine flowmeter, a conductance sensor, and an optical fiber sensor in a simulation well. Sensor response characteristics were researched, and a new method of measuring the oil–air–water three-phase flow rate was proposed. The measurement range and resolution of the gas flow rate were 3–20 and 1 m 3 /d, respectively, and the relative error range of gas flow rate interpretation was 5–10%. The measurement range and relative interpretation error range of the total liquid flow rate were 10–60 m 3 /d and 5–10%, respectively. The measurement range and resolution of the water cut were 50–100% and 2%, respectively. The absolute error range of interpretation of the water cut ranged from 3.2% to 5%. Currently, the technique is valid for laboratory use under ideal conditions.